Resistencia a la fractura radicular en dientes reforzados con ionomero de vidrio resino-modificado y restaurados con poste y cofia colados - Cuartas-Estrada, María Elena; Escobar-Restrepo, Julio César; Muñoz-Rodríguez, Francisco César; Castaño-Granada, María Catalina (Revista Facultad de Odontología Universidad de Antioquia, 2020)
This in-vitro study was aimed to examine how a composite-modified glass ionomer behaves when used as a reinforced cement for weak dentin walls in thirty lower first bicuspids treated endodontically and prepared for restoration with metal core and post. Those thirty teeth were randomly assigned to one of three different groups, as follows: Group 1: ten endodontically treated teeth, restored with metal core and post. Group 2: ten endodontically treated teeth, structurally weakened on purpose, restored with metal core and post. Group 3: ten endodontically treated teeth, structurally weakened on purpose, reinforced with a composite-modified glass ionomer, and restored with metal core and post. Ah teeth were submitted to compressive forces, in an Instrom device, which registered the whole complex behavior in a strength vs. deformity graphic. Through non parametric statistical tests (Median, Mann Whitney), no statistically significant difference was found for the compressive force levels at which teeth fractured on every group (P < 0.05). In spite of any physical or chemical virtue glass ionomers may have (some said to be tooth structure alike), their usefulness in destroyed zones to reinforce teeth couldn't be confirmed.